Assessing food web structure in relation to nutrient enrichment, macrophyte collapse and lake resilience in shallow lowland lakes - David J. Kelly; Marc Schallenberg (New Zealand Journal of Marine and Freshwater Research, 2019)
We examined food chain length and food web complexity as indicators for assessing shallow lake resilience from 18 lowland lakes, which included lakes in near‐reference condition through to lakes that had undergone catastrophic regime shifts. We observed a trend of decreasing food chain length and food web complexity in lakes that had undergone regime shifts. Across the full trophic gradient, food web metrics were correlated with factors related to trophic status (e.g. chlorophyll‐a) and macrophyte loss (e.g. exotic herbivorous fish), which have been previously associated with regime shifts in lakes. With increasing eutrophication, we identified a shift away from omnivory mostly in the lower trophic levels. Factors that impinge on macrophyte communities, such as nutrient loading and herbivory, reduce the resilience of shallow lake ecosystems, which is reflected in changes to lake food web structure. Thus, food web indicators can inform about the sensitivity of shallow lakes to eutrophication.